The cardiac lymphatic system : an overview - Karunamuni, Ganga (Springer New York, 2013)
The Cardiac Lymphatic System: An Overview provides in-depth coverage of the cardiac lymphatic vessels and the essential nature of their patterning and development in the heart tissue. The volume is organized into three sections: the anatomy of the cardiac lymphatic system, the cardiac lymphatics and heart disease, and cardiac lymphatic signaling. The content of this book will be useful to a broad audience interested in cardiovascular medicine and physiology, including clinicians, students, and researchers in the fields of developmental biology, cardiology and applied anatomy. The groundwork in this book will be able to provide readers with vital information on the crucial role played by the cardiac lymphatic vessels in preserving normal heart function.